2021
DOI: 10.1021/acsbiomaterials.1c00635
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Effects of Synergistic Thermal and Photo-Cross-Linking during Biofabrication on the Structural and Functional Properties of Gelatin Methacryloyl (GelMA) Hydrogels

Abstract: Gelatin methacryloyl (GelMA) hydrogels have emerged as promising and versatile biomaterial matrices with applications spanning drug delivery, disease modeling, and tissue engineering and regenerative medicine. GelMA exhibits reversible thermal cross-linking at temperatures below 37 °C due to the entanglement of constitutive polymeric chains, and subsequent ultraviolet (UV) photo-cross-linking can covalently bind neighboring chains to create irreversibly crosslinked hydrogels. However, how these cross-linking m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…The pore sizes were determined from CryoSEM images (3500X magnification) using a custom algorithm in MATLAB that we developed in our previous work. [43] Assessment of Viability and Elongation of Cells in Pure GelMA Constructs under Different Thermo-Reversible and Photocrosslinking Conditions: For the study shown in Figure 2, the media above the constructs in the 24-well plates was extracted and 1 mL of PBS containing Live/Dead assay reagents (L3224, Thermo Fisher) at a concentration of 0.25 μL mL −1 for calcein-AM and 1 μL mL −1 of ethidium homodimer-1 added. The constructs were then washed and imaged using fluorescence microscopy (SP8, Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pore sizes were determined from CryoSEM images (3500X magnification) using a custom algorithm in MATLAB that we developed in our previous work. [43] Assessment of Viability and Elongation of Cells in Pure GelMA Constructs under Different Thermo-Reversible and Photocrosslinking Conditions: For the study shown in Figure 2, the media above the constructs in the 24-well plates was extracted and 1 mL of PBS containing Live/Dead assay reagents (L3224, Thermo Fisher) at a concentration of 0.25 μL mL −1 for calcein-AM and 1 μL mL −1 of ethidium homodimer-1 added. The constructs were then washed and imaged using fluorescence microscopy (SP8, Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
“…The GelMA used in this study was purchased in a lyophilized form (80% degree of substitution (DOS), 900 496, Millipore Sigma). The consistency of DOS across different purchased batches was verified using 1 HNMR spectroscopy [ 43 ] to be within ±7.5%. The lyophilized GelMA was constituted at 5% w/v in phosphate buffered saline (PBS) and the photoinitiator Lithium phenyl‐2,4,6‐trimethylbenzoylphosphinate (LAP) added at a concentration of 0.25% w/v to formulate the pure GelMA photoink.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the liquid can cool down very rapidly with such a small volume. Several studies found that cooling down a GelMA pre-gel solution to temperatures below 25 °C before crosslinking actually increased the elastic modulus of the crosslinked hydrogel compared to crosslinking the pre-gel solution directly at RT (Rizwan et al, 2017;Young et al, 2020;Chansoria et al, 2021). This is due to the physical gelation of the gelatine before light-curing, which induces a better organisation of the gelatine chains resulting in a higher crosslinking density.…”
Section: Optimisation Of the Gelation Conditions And Mechanical Chara...mentioning
confidence: 99%